Simulation of Doped Si Oxidation in Nano-dimension Scale - Kersys, T.; Anilionis, R.; Eidukas, D. (Elektronika ir Elektrotechnika, 2008)
The fabrication of microelectronic structures and devices vitally depends on the thermal oxidation. It is observed that thickness of SiO2 layer getting uneven when oxidizing doped Si areas by various dopants. It was defined that dopants determinate SiO2 formation in thermal oxidation technological process. Dimension is very important parameter in nano-technologies therefore doping dependent oxidation makes additional problems when forming nano-structures. By using mathematical simulation program ATHENA was performed mathematical simulation of Si thermal oxidation, and was evaluated the Si substrate doping dependent oxidation. Ill. 12, bibl. 7 (in English; summaries in English, Russian and Lithuanian).